Introduction to Strategic Management Concepts and Tools - Abd Rahman Ahmad (Penerbit UTHM, 2024)
Looking to gain an edge in the competitive world of business? Look no further than “Introduction to Strategic Management: Concepts and Tools”! This book is your ultimate guide to the exciting field of strategic management, packed with everything you need to know to develop winning strategies and achieve lasting success. Through its engaging and easy-to-read content, this book provides a comprehensive overview of the strategic management process, highlighting key concepts and tools that are essential for creating effective strategies. You’ll discover the most popular strategy approaches and tools used by top organizations worldwide to formulate, implement and evaluate their strategic plans, ultimately helping them to gain a sustained competitive advantage in their respective markets. This book also provides a detailed understanding of the most important tools used in the strategic management process. Each chapter is thought fully presented in a logical order, making it easy for you to follow along and apply the concepts to your own business. Best of all, the author welcomes your suggestions for improving the book’s contents, ensuring that it remains up-to date and relevant for years to come. Grab your copy today and start taking your business to the next level!